2007
DOI: 10.1002/pca.975
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polyphenolic compounds and radical scavenging activity of four American Actaea species

Abstract: A reversed-phase high-performance liquid chromatography (RP-HPLC) method with diode array detection has been developed for analysis of the major polyphenols in the roots and rhizomes of black cohosh (Actaea racemosa), an important botanical dietary supplement for women's health, and three closely related American Actaea species, A. rubra, A. pachypoda and A. podocarpa. The method was validated with respect to sensitivity, linearity, precision, accuracy and recovery. The total content of eight major polyphenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…The HPLC-UV fingerprint of them has been used to distinguish A. racemosa from major American and Asian Actaea species [11, 21]. The current study demonstrated that the EIC profile in MS positive mode of these five hydroxycinnamic acid esters could also distinguish A. racemosa from the other two American species and two Asian adulterants successfully, as shown in Fig.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…The HPLC-UV fingerprint of them has been used to distinguish A. racemosa from major American and Asian Actaea species [11, 21]. The current study demonstrated that the EIC profile in MS positive mode of these five hydroxycinnamic acid esters could also distinguish A. racemosa from the other two American species and two Asian adulterants successfully, as shown in Fig.…”
Section: Resultssupporting
confidence: 53%
“…Despite increasing consumption and extensive investigation, the mechanisms of its alleviation of climacteric symptoms remain largely undefined [911]. The phytochemical constitution of black cohosh is complex and the active ingredients remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[30] A similar method for isolating CGA has been reported for flowers of L. japonica (honeysuckle) using HPD-850 chromatography. [16] Following elution with 70% ethanol, the CGA content of the honeysuckle extract increased 4.5 fold.…”
Section: Resultsmentioning
confidence: 99%